The Effect of Radiation Protection Provided by Lead Aprons in Orthopedic Theater - Murad Hammed; Waleed Abdulwahid (University of Kirkuk, College of Medicine, Kirkuk, Iraq, 2024)
Background: Orthopedic surgeons and operation staff are exposed to intraoperative radiation routinely because modern medicine is unthinkable without X-rays. Along with their advantages X-rays have also a harmful effect. This needs special care to be taken to protect from this radiation. Several factors that influence exposure risk have been identifiedincluding type of surgery, distance from radiation source, subspecialty practiced, and experience level of the surgeon. The aim of this study is to measure the effective protection provided by lead aprons and thyroid shields in orthopedic theater during surgical operations.Methods: Radiation dose was measured during the use of a C-arm on an anthropomorphic lower thigh and proximal leg phantom on the operating table and scatter radiation exposure to multiple organs (thyroid, breast, gonads) and direct radiation exposure to the hands measured by Geiger Muller counter 300E plus (GMC300E plus) in different positions of the C arm and from different distances from radiation source.Results: Scattered radiation exposure is higher when the C arm is in an inverted position and horizontal position when the Geiger is at the side of emitter and close to the C arm. Radiation exposure dose decreases as increasing the distance from the C arm. Lead aprons and thyroid shields decrease radiation exposure by approximately 90%.Conclusion: The efficacy of radiation protection in orthopedic theaters is closely tied to the wearing of lead aprons, including thyroid shields, and the positioning of both the surgeon and the surgical staff in relation to the C-arm. Conversely, radiation exposure tends to increase when the C-arm is inverted or positioned horizontally.